Peran guru untuk menerapkan pembelajaran sejarah di sekolah menengah atas - Triasih Kartikowati; Kurniawati Kurniawati; Nurzengky Ibrahim (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study aims to provide an understanding of multiculturalism in the classroom and the prospects for teachers applying it in history lessons. The number of students in the school already represents the diversity that exists, consisting of a variety of ethnicities, cultures, customs and religions. The teacher's emphasis on implementing multiculturalism in learning is an embodiment of the values of Pancasila as the ideology of the Indonesian nation which stands on the basis of diversity, tolerance with the motto Bhineka Tunggal Ika. Indonesia is often hit by inter-community conflicts and violence which can lead to divisions, be it ethnic conflicts or conflicts between religious adherents. Existing diversity often results in discrimination that leads to conflict and violence. The importance of the aspect of multiculturalism in view of the diverse conditions of Indonesian society demands mutual tolerance, respect and respect for these various differences. By using the method, a qualitative research approach and a case study approach at SMA Negeri 20 Jakarta, DKI Jakarta. The results of the study are supported by an independent curriculum reference which requires schools to apply the dimensions of the Pancasila Student Profile, teachers practice directly in implementing multiculturalism education and create a multicultural learning culture and are able to generate student motivation. In practice, the teacher groups students according to the wishes, talents and interests of students. Implementation of the educational value of multiculturalism students create video content and pop-up book projects with Indonesian historical material such as tolerance, maintaining diversity, pluralism and multiculturalism.